PERENCANAAN GEDUNG SINEMA KELUARGA DI KAWASAN PULAU KUMALA PENEKANAN PADA AKUSTIK RUANG - Bhanu Rizfa Hakim; Anna Rulia; Arif Indra Fahlafi (Indonesian Society of Applied Science, 2021)
The development of the cinema industry in the city of Samarinda and the development increased significantly. At present, in the city of Samarinda there are 5 famous brand places, namely XX1 Big Mall, XX1 Samarinda Square, XX1 SCP, Cinema 21 SCP, and the newest CGV Cinema Plaza Mulia. The number of developments in East Kalimantan, especially Samarinda and its surroundings was triggered by a considerable attraction from the public for the film industry, from children to the elderly. This gives the potential for regional economic growth from the tourism sector. Therefore, this potential needs to be maximized by involving the construction of the Family Cinema Building in the Kumala Island Region, housing and entertainment clusters, Tenggarong City, Kutai Kartanegara Regency, East Kalimantan. This great potential is supported by the strategic tourism area of ​​Kumala Island and the absence of well-known brands in the city of Tenggarong. In addition, Kumala Island as a tourist island that needs to be managed and benefited by the Government and the Tourism Department of Kutai Kartanegara Regency is an attractive tourist attraction for the surrounding community and migrants. Planning this Family Cinema Building will be one of the best attractions for the community, because it supports the family concept, providing 17 mini theater spaces, lounges, parks and other facilities. So the planning of tourist attraction development needs to be done in order to maximize the essence and image of Kumala Island as one of the best tourist destinations in East Kalimantan.